Diseminasi Fertigasi Otomatis Nirdaya untuk Budidaya Sayuran di Kota Tasikmalaya - Riani Muharomah; Budi Indra Setiawan; Suwardi Suwardi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Unpowered Automatic Fertigation (FONi) is a new technology developed by IPB University. FONi applies the concept of evapotranspiration irrigation, which can meet plants' water needs at any time without using electricity. FONi is a series of plant pots connected to a water supply tank, and the water level is maintained to form a connected vessel system. The nutrient solution can be put into a water tank to make fertilizer application more practical. This activity aims to introduce FONi to the broader community so that it can utilize non-productive land for planting valuable vegetables and getting feedback for further development. Types of vegetables cultivated are long beans intercropped with kale. This activity was carried out in a residential area located on Jl. Burujul II, RW 03, Cipedes, Tasikmalaya City, West Java. Activities range from designing, installing, planting, maintaining, observing, harvesting, and explaining to the community, local government, and mass media. After 14 days, kale was picked, while long beans were picked after 48 days. Within 48 days, the prolonged bean harvest reached 3 Kg with land and water productivity of 2.9 kg m-2 and 2.3 kg L-1, respectively. CCTV monitoring shows prolonged bean picking is still carried out for up to 60 days. The economic value of cultivating long beans and kale in one season exceeds the cost of construction and production. The public's interest is high, implied by a strong desire to apply it. If this activity continues, it is hoped that the nutritional needs and adequacy of safe and healthy vegetables for all residents in the future can be fulfilled and that it will strengthen the image of Tasikmalaya City as a Kota Resik.